2010
DOI: 10.1038/jhg.2010.115
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the MYO7A and CDH23 genes in Japanese patients with Usher syndrome type 1

Abstract: Usher syndrome (USH) is an autosomal recessive disorder characterized by retinitis pigmentosa and hearing loss. USH type 1 (USH1), the second common type of USH, is frequently caused by MYO7A and CDH23 mutations, accounting for 70-80% of the cases among various ethnicities, including Caucasians, Africans and Asians. However, there have been no reports of mutation analysis for any responsible genes for USH1 in Japanese patients. This study describes the first mutation analysis of MYO7A and CDH23 in Japanese USH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…PCDH15 :c.158-1G>A, predicted to alter the splice donor site of intron 3, has been classified as pathogenic. MYO7A :p.Ala771Ser is a non-truncating mutation, but was previously reported as disease-causing [13]. So, we consider the patient to be the first reported case of MYO7A / PCDH15 digenic inheritance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…PCDH15 :c.158-1G>A, predicted to alter the splice donor site of intron 3, has been classified as pathogenic. MYO7A :p.Ala771Ser is a non-truncating mutation, but was previously reported as disease-causing [13]. So, we consider the patient to be the first reported case of MYO7A / PCDH15 digenic inheritance.…”
Section: Discussionmentioning
confidence: 84%
“…In Caucasian USH1 patients, previous studies showed that mutations in MYO7A , USH1C , CDH23 , PCDH15 , and USH1G , were found in 39–55%, 7–14%, 7–35%, 7–11%, and 0–7%, respectively (the frequency of CIB2 is still unknown) [10], [11], [12]. In Japanese, Nakanishi et al showed that MYO7A and CDH23 mutations are present in USH1 patients [13], however, the frequency is not yet known. In addition, mutations in three corresponding genes (usherin USH2A [14], G protein-coupled receptor 98; GPR98 [15], and deafness, autosomal recessive 31; DFNB31 [16]) have been reported so far in USH2, and USH3 is caused by mutations in the clarin 1 ( CLRN1 ) [17] gene.…”
Section: Introductionmentioning
confidence: 99%
“…MYO7A is the major gene responsible for USH1 and mutations in MYO7A alone account for 70% of USH1. CDH23 is the second commonly mutated gene and mutations in MYO7A and CDH23 together account for 80% of USH1 [11], [12]. Mutations in three genes, USH2A [ 13 ], GPR98 [ 14 ], and DFNB31/WHRN [ 15 ] have been identified as disease-causing for USH2.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in these genes affect the pressure-sensitive stereocilia of the inner ear (Hereditary Hearing Loss Homepage, http://hereditaryhearingloss.org/) and do not occur at the same frequencies across ethnicities. Of all pathogenic mutations, 29∼55% are in the MYO7A gene [4], [5], [6], [7], [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%